(untitled) (GIST – Education and Learning Research Journal, 2018)
In EFL composition courses, teaching and learning normally orbit around norms of unity, coherence, support, and sentence skills that L2 learners are expected to comply with, at the expense of opportunities to develop voice. Against this backdrop, we resolved to examine the extent to which students’ exposure to and practice with lexical bundles, boosters/hedges and stance-taking strategies allows them to build a stronger discoursal and authorial voice as future academic writers. Evaluation of the students’ works revealed their level of success in this endeavor and analysis of student surveys unveiled the tensions and struggles they faced along the way. At the end of this paper, we advocate for academic writing courses to be transformed into spaces where students not only come to terms with the basic norms they have to conform to, but also build a discoursal and authorial voice as L2 writers.